The natural resources of East Africa - Russell, E. W.; East African Literature Bureau (Nairobi : D.A. Hawkins, in association with East African Literature Bureau, 1962)
This handbook has been prepared at the request of the Chief conservators of forests of East Africa to mark the opening of the eighth commonwealth forestry conference, the book contains information of general interest about East Africa.
Part of illustrative matter fold. in pocket.
Bibliography: p. 101-102.
hza 19/02/2019
Loans
Keywords: Natural resources; Africa, East